Effect of Hydroalcoholic Leaf Extract of Leucas aspera on Lead Acetate Induced Alterations in Membrane Bound Enzymes - Dhanalakshmi, M (International Journal of Pharmaceutical & Biological Archive, 2013)
Effect of Hydroalcoholic Leaf Extract of Leucas aspera on Lead Acetate Induced Alterations in Membrane Bound Enzymes